2006
DOI: 10.1097/01.sla.0000220042.48310.66
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 80-Hour Resident Workweek on Surgical Residents and Attending Surgeons

Abstract: Although the mandated restriction of resident duty hours has had no measurable impact on the quality of patient care and has led to improvements for the current quality of life of residents, there are many concerns with regards to the training of professional, responsible surgeons for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
246
2
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(273 citation statements)
references
References 24 publications
7
246
2
18
Order By: Relevance
“…Competing demands are motivating a better understanding of surgical processes: surgical procedures are getting more complex [2], residents now have to be trained while performing less procedures [3], the surgical interventions have to be more and more justified [4] and the procedures have to cost less money [5], et caetera. A better understanding of surgical practices is the key component to addressing these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Competing demands are motivating a better understanding of surgical processes: surgical procedures are getting more complex [2], residents now have to be trained while performing less procedures [3], the surgical interventions have to be more and more justified [4] and the procedures have to cost less money [5], et caetera. A better understanding of surgical practices is the key component to addressing these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Working-time restriction is mainly investigated in US residents. In most studies, burnout scores decreased significantly with reduced working-time [2123]. Literature is inconclusive whether this decrease is a consequence of weekly working-time restrictions or a restriction in shift length.…”
Section: Discussionmentioning
confidence: 99%
“…11 Search of the references of these studies identified another 14 citations. With further analysis, articles were selected wherein interventions relevant to one or more of the three themes were studied, resulting in a final selection of 56 citations Twenty-one studies analyzed transitions in, during, and after residency education; 19 studies addressed the educational effects of duty hour limits, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 16 articles presented research on use of the competencies in teaching and assessing anesthesiology residents. [19][20][21][22][23][24][25][26][27][52][53][54][55][56][57][58] For the theme ''duty hours and the acquisition of competence'', the only articles included were those that assessed the effect of duty hour limits on measures of physician competence and those that studied changes in patient care experience in anesthesiology that could be attributed to the reduction in resident hours.…”
Section: Methodsmentioning
confidence: 99%
“…One national study 36 and two single institution studies 37,38 found improved scores in the in-training exam in surgical specialties. In a national study of orthopedic surgery residents, 39 three single institution studies in surgery and otolaryngology, [40][41][42] and an older study of the impact of New York state's duty hour regulation on obstetricsgynecology residents 40 showed no changes in in-training exam performance. Among the three studies that assessed the effect of the duty hour reduction on board certification in surgical programs, declining performance was found in a national study of surgery residents 44 and a single institution study of neurological surgery residents, 45 and no change was found in a second single institution study of surgery residents.…”
Section: Duty Hour Limits and The Acquisition Of Competencementioning
confidence: 99%